Geographic Variation in Religiosity and its Impact of Dividend Policies - Omar Farooq; Mukhammadfoik Bakhadirov; Neveen Ahmed (Asian Academy of Management Journal of Accounting and Finance, 2020)
The main aim of this research is to document the relationship between geographical variations in the religiosity levels and the dividend policies adopted by firms. Using the data provided by the Gallup International, we test our arguments on the firms headquartered in different states of the United States. Our results show that firms headquartered in states with high level of religiosity have higher payout ratios than firms headquartered in states with low level of religiosity. These are results are robust across various proxies of religiosity and dividend policies (decision to pay dividend, decision to increase dividend, and dividend yield). We also show that value of dividend payouts is higher in states with high level of religiosity. We extend prior literature by also documenting the moderating role of religiosity for the value of dividend policy.